NUMERICAL ANALYSIS OF INDIRECT ICE STORAGE SYSTEMS PERFORMANCE - Stampa, C. S.; Nieckele, A. O. (Revista de Engenharia Térmica, 2006)
A numerical investigation regarding the charging process behavior occurring in a typical indirect ice storage tank is presented. It consists of analyzing the heat transfer and removal of energy, applicable to storage systems, which are chiller-based. In this sense the secondary coolant circulates through a heat exchanger that is submerged in a tank of water and it is used to freeze (charge) the phase-change material (water), which never leaves the storage tank. The thermal exchange process is investigated considering the storage tank in two different positions. In the first one the storage tank is in the vertical position, while for the second, it is horizontally positioned. The storage tank is represented by a channel formed by parallel flat plates, one of which is the heat exchanger. Our task is to provide helpful qualitative results for the heat transfer performance of ice storage tanks. The results are analysed through streamlines and isotherms, for specific instants of time. Further, the heat transfer effectiveness, average heat flux and solid formed at one of the two plates of the channel, are compared for the vertical and horizontal positions of the channel.